Impacts of roundabouts in suburban areas on congestion-specific vehicle speed profiles, pollutant and noise emissions: an empirical analysis - Fernandes, P. (2020)
Increasing concern about global warming and air quality has meant an increasing use of energetic and environmental indicators in roundabout design. This research compares different suburban roundabouts in terms of traffic performance, pollutant and noise emissions through an integrated empirical assessment. Field measurements were carried out with a light duty vehicle in single-lane (SL), compact two-lane (CTL) and multi-lane (ML) roundabouts using Portable Emission Measurements Systems, OBD scan tool and Sound Level Meter, to measure real-world exhaust emissions, engine activity and acoustic data, respectively. Afterwards, predictive discrete models that correlate the probability of speed profiles (no stop, stop once and multiple stops) with roundabout operational parameters were developed. Although SL yielded the lowest CO2 per vehicle, its implementation resulted in high LAeq because vehicles drove at moderate speeds in the approach and low conflicting traffic compared to other layouts. CTL was the worst option in terms of both CO2 and NOX. The proposed methodology can be tailored in other roundabouts in suburban areas with similar layouts by simply identifying their traffic volumes and representative speed profiles. This can help researchers, traffic planners or practitioners to reduce congestion and emissions, and enhance road traffic management near urban areas.